TPZ, a bright centrosymmetric two-photon scaffold for bioimaging12. Issue 79 (21st September 2017) - Lei, Zuhai; Yue, Ping; Wang, Xueli; Li, Xinran; Li, Yi; He, Haihong; Luo, Xiao; Meng, Xiangming; Chen, Jinquan; Qian, Xuhong; Yang, Youjun
Abstract : The development of biocompatible two-photon fluorophores with a large absorption cross-section is challenging, despite the presence of theoretical guidelines. Abstract : The development of biocompatible two-photon fluorophores with a large absorption cross-section is challenging, despite the presence of theoretical guidelines. By rendering asymmetric PRODAN dye centrosymmetric, we designed and synthesized a novel class of two-photon fluorophores (TPZ ). Their photophysical properties were investigated and their imaging potentials in cells, tissues and zebrafish were showcased.